Monitoring Of Ground-Level Ozone At Roadside In Pulau Pinang Josiah Yong Say Jee - Yong , Josiah Say Jee (2011)

(untitled)
First and foremost, I want to thank God for giving me the opportunity to further my studies and carry out this research. I would like to greatly appreciate my supervisor Associate Professor Dr. Nor Azam Ramli for his willingness to accept me under his supervision and putting in effort in assisting me throughout my research. He has given me valuable feedbacks and inputs throughout my study. Next, I would like to express my sincere gratitude to Associate Professor Ahmad Shukri Yahya, Dr. Nurul Adyani and Dr. Faizah Fitri for their helpfulness in the area of data analysis involving the SPSS software and advices given to me. Also, I would like to appreciate my fellow colleague Loh Gnai Chun for putting in great effort by assisting me in the area of data collection. Another group of people I would like to express my heartfelt thanks would be all my fellow coursemates, housemates and friends for their helpfulness, understanding and support. Last but not least, I wish to thank my family members for their never ending love, concern, encouragement and support throughout my entire study.